A Plyometric Warm-Up Protocol Improves Running Economy in Recreational Endurance Athletes - Wei, ChenGuang; Yu, Liang; Duncan, Benedict; Renfree, Andrew (Frontiers in Physiology, 2020)
The study which compared the effectiveness of the two warm-up protocols in healthy adults determined whether acute resistance warm-up and plyometric warm-up can improve running economy. 12 healthy colleague students (3 males, 9 females, age 20±2 years, maximal oxygen uptake (38.4± 6.4 ml.kg-1 min-1) who had not regular and systematic endurance training history with the training time less than 5 hours per week volunteered to participant in this study. All the participants completed three different warm-up protocols (control, plyometric and resistance warm-up) in a counterbalanced crossover design with trials separately 48 hours, using a Latin-square arrangement. Dependent variables measured in this study were RE at four running velocities (7, 8, 9 and 10km h-1), maximal oxygen uptake; heart rate; respiratory exchange rate; expired ventilation; perceived race readiness; rating of perceived exertion, time to exhaustion and leg stiffness. The primary finding of this study was that plyometric warm-up can improve running economy (6.2% at the velocity of 7km h-1, ES=0.66, 9.1% at the velocity of 8km h-1, ES=0.71, 4.5% at the velocity of 9km h-1, ES=0.48, and 4.4% at the velocity of 10km h-1, ES=0.44). Additionally, compared with the control and resistance warm-up protocols, there were no statistical significant changes in other metabolic and pulmonary gas exchange indicators; time to exhaustion; perceived race readiness and maximal oxygen uptake following the plyometric warn-up. However, the leg stiffness showed a 20% (P=0.039, ES=0.90) increase following the plyometric warm-up and it was correlated to the improved running economy at the running velocity of 8km h-1 (r=0.475, P<0.05). Moreover, no significant statistical differences in running economy were found between control and resistance warm-up protocols. In comparison with the control and resistance warm-up protocols, an acute plyometric warm-up protocol can improve running economy in healthy adults. In addition to this, only two participants showed improvements in running economy following the resistance warm-up. The possible reason may be derived from the unsuitable intensity used in this study. Keywords: Plyometric1, Resistance2, Warm-up3, Leg stiffness4, Post-activation potentiation5, Running economy6